Evaluating the "keep your health plan fix" : implications for the Affordable Care Act compared to legislative alternatives - Saltzman, Evan (Rand Corporation, 2014)
This report describes a comparative analysis of three proposals to remedy the situation: one by the White House, another by Senator Mary Landrieu (D-LA), and a third by Representative Fred Upton (R-MI). The proposals are evaluated based on their potential impact on the ACA-compliant market and the cost and coverage of health insurance. The possibility of each proposal causing a "death spiral," in which rising premiums and decreasing enrollment undermine the viability of the ACA-compliant market, is also addressed. The authors find that the three proposals vary from slight to moderate impact on ACA premiums, enrollment, and federal spending, but none of them would result in the unraveling of the ACA-compliant market